Determinants and value of corporate social responsibility management: Empirical evidence from the insurance industry - Tim Brasch; Christian Eckert (Risk Management and Insurance Review, 2024)
The aim of this paper is to empirically study corporate social responsibility management in the insurance industry, which has received increased attention in recent years. For this purpose, we use data from LSEG (former REFINITIV) over a period of 11 years (2010–2020) taking into account companies from the United States, Europe, China, and Japan, and analyze the determinants and the value of corporate social responsibility management. Our results show that larger insurers exhibit significantly better corporate social responsibility management. Moreover, focusing on the recent past we find an indication of the value-relevance of a holistic corporate social responsibility management. Hence, our findings reveal that it might be economically rational for insurance companies to become more sustainable. Therefore, it might be that the insurance market is able to move towards a more sustainable direction on its own, finally, reducing the importance of regulatory interventions in this regard.
Keywords: 330